Implementasi dan Penegakan Hukum Tata Negara dalam Konteks Globalisasi - Mardiyati, Siti (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
Globalization has brought significant changes to various aspects of life, including in the field of constitutional law. The implementation and enforcement of constitutional law in the context of globalization, focusing on how global dynamics influence national legal structures and their enforcement mechanisms. Globalization, characterized by the openness of information, the movement of capital, and the flow of international labor, demands that countries adjust their constitutional legal systems to meet new challenges, such as human rights, democratization, and free trade. On one hand, globalization encourages the harmonization of laws at the international level, while on the other hand, it amplifies the risks of violations of state sovereignty and disparities in the application of laws. This research reveals that the implementation of constitutional law often faces challenges in maintaining a balance between national interests and global demands. This requires strengthening the role of domestic legal institutions, as well as collaboration with international actors and civil society. In the era of globalization, civil society and international organizations also play a crucial role in overseeing and promoting transparency and accountability in the process of upholding constitutional law. To maintain the effectiveness of constitutional law enforcement, dynamic policy adaptation, active participation from various stakeholders, and the use of technology to strengthen the integrity of the legal system are necessary.